STRATEGI UNTUK MERAIH KEUNGGULAN KOMPETITIF DALAM E-BUSINESS: STUDI KASUS PADA META - Sikki, Nurhaeni; Sari, Desi Mayang; Putri, Anugera Septidwi; Supriadi, Eddi; Nurjaman, Maman; Haerunnisa, Indah; Firmansyah, Muhammad Lutfi; Wagino, Wagino; Wahyuni, Silvy Dwi (Journal of Information System, Applied, Management, Accounting and Research, 2025)
The internet has experienced phases of growth, decline and growth again. Not many companies that are involved in E-Business are able to adapt to the life cycle experienced by the internet. One company that is able to adapt and succeed in doing business in the internet life cycle is Meta Platforms. This article tries to identify strategies built by Meta Platforms to achieve competitive advantage in doing business in the internet era. This paper finds that Meta Platforms implements a strategy by building technological infrastructure and acquiring various media that enable people to connect, share and collaborate more easily in cyberspace so that it can help people connect and share what they want with anyone in the world . The strategy built by Meta Platforms is able to bring competitive advantage by forming new "rules" in online business (E-Business) competition.